Abordando o ensino de óptica através da construção de telescópios - Bernardes, Tamara O. [UNESP] (2006)
The scope of this work is the manufacturing of reflective telescope of Newtonian type, relating issues treated in optics classes, such as image formation, chromatic and spherical aberrations, interference and dirraction, with each step of the building process. The built equipment allows analyzing lunar and planetary photography with high resolution, and its use by high school students gives a great motivation to sky contemplation, as well as the understanding of several physical phenomena, generally poorly treated in public schools. Besides the telescope itself, the software produced by undergraduate students has also been used as an efficient tool in astronomy teaching, mainly to first-level students. Copyright by the Sociedade Brasileira de Física.